On the method of state invariance - Toan, Nguyen Canh; Lap, Do Van (Journal of Computer Science and Cybernetics, 2016)
This paper develops a lena-kumpati methodology for the design of adaptive control systems which guarantee the state invariance of the plant although there is invariance in its work condition.